Trellis-coded modulation with bit interleaving and iterative decoding. - Xiaodong Li
This paper considers bit-interleaved coded modulation (BICM) for bandwidth-efficient transmission using software radios. A simple iterative decoding (ID) method with hard-decision feedback is suggested to achieve better performance. The paper shows that convolutional codes with good Hamming-distance property can provide both high diversity order and large free Euclidean distance for BICM-ID. The method offers a common framework for coded modulation over channels with a variety of fading statistics. In addition, BICM-ID allows an efficient combination of punctured convolutional codes and multiphase/level modulation, and therefore provides a simple mechanism for variable-rate transmission
Keywords: AWGN channels; Hamming-distance property; Rayleigh fading channels; Bandwidth-efficient transmission; Bit-interleaved coded modulation; Convolutional codes; Fading statistics; Hard-decision feedback; High diversity order; Iterative decoding; Large free Euclidean distance; Multiphase/level modulation; Performance; Punctured convolutional codes; Software radios; Trellis-coded modulation; Variable-rate transmission